Antitumor activity of Type I and Type III interferons in BNL hepatoma model - Abushahba, Walid (Cancer Immunol Immunother, 2010)
Hepatocellular carcinoma (HCC) occurs most commonly secondary to cirrhosis due to chronic hepatitis C or B virus (HCV/HBV) infections. Type I interferon (IFN-α) treatment of chronic HCV/HBV infections reduces the incidence of HCC in cirrhotic patients. However, IFN-α toxicity limits its tolerability and efficacy highlighting a need for better therapeutic treatments. A recently discovered type III IFN (IFN-λ) has been shown to possess antiviral properties against HCV and HBV in vitro. In phase I clinical trials, IFN-λ treatment did not cause significant adverse reactions. Using a gene therapy approach, we compared the antitumor properties of IFN-α and IFN-λ in a transplantable hepatoma model of HCC. BALB/c mice were inoculated with syngeneic BNL hepatoma cells, or BNL cells expressing IFN-λ (BNL.IFN-λ cells) or IFN-α (BNL.IFN-α cells). Despite the lack of antiproliferative activity of IFNs on BNL cells, both BNL.IFN-λ and BNL.IFN-α cells displayed retarded growth kinetics in vivo. Depletion of NK cells from splenocytes inhibited splenocyte-mediated cytotoxicity, demonstrating that NK cells play a role in IFN-induced antitumor responses. However, isolated NK cells did not respond directly to IFN-λ. There was also a marked NK cell infiltration in IFN-λ producing tumors. In addition, IFN-λ and, to a lesser extent, IFN-α enhanced immunocytotoxicity of splenocytes primed with irradiated BNL cells. Splenocyte cytotoxicity against BNL cells was dependent on IL-12 and IFN-γ, and mediated by dendritic cells. In contrast to NK cells, isolated from spleen CD11c+ and mPDCA+ dendritic cells responded directly to IFN-λ. The antitumor activities of IFN-λ against hepatoma, in combination with HCV and HBV antiviral activities warrant further investigation into the clinical use of IFN-λ to prevent HCC in HCV/HBV-infected cirrhotic patients, as well as to treat liver cancer.